Analisis Pengaruh Perceived Quality Terhadap Brand Trust, Brand Attachment, dan Brand Commitment (Studi Pada Pengguna Smartphone Samsung) - Reno Vancasavio; Farida Indriani (Forum Manajemen Indonesia (FMI), 2017)
This study aims to analyze perceived quality towards brand trust, brand attachment, and brand commitment to smartphone users especially Samsung. The reasons why using perceived quality as a variable because it has direct role to the users that takes a parts of having Samsung smartphone. Non-probability technique was used for sampling and the population are Samsung smartphone users that has 18-24 years old range. Data were collected from 150 respondents which were selected using criteria of judgments that should has Samsung as their smartphone for minimal one year and students at Semarang. Test method is a Maximum likelihood analysis with AMOS program version 21.0. The results showed that perceived quality variable directly giving positive influence towards brand trust, brand attachment, and brand commitment. Since three of the variables that have been influenced by perceived quality, one of the most influenced by perceived quality is brand trust. Keywords: Perceived Quality, Brand Trust, Brand Attachment, and Brand Commitment